What can be lost? Genomic perspective on the lipid metabolism of Mucoromycota - Blanka Sokołowska; Małgorzata Orłowska; Alicja Okrasińska; Sebastian Piłsyk; Julia Pawłowska; Anna Muszewska (IMA Fungus)
Abstract Mucoromycota is a phylum of early diverging fungal (EDF) lineages, of mostly plant-associated terrestrial fungi. Some strains have been selected as promising biotechnological organisms due to their ability to produce polyunsaturated fatty acids and efficient conversion of nutrients into lipids. Others get their lipids from the host plant and are unable to produce even the essential ones on their own. Following the advancement in EDF genome sequencing, we carried out a systematic survey of lipid metabolism protein families across different EDF lineages. This enabled us to explore the genomic basis of the previously documented ability to produce several types of lipids within the fungal tree of life. The core lipid metabolism genes showed no significant diversity in distribution, however specialized lipid metabolic pathways differed in this regard among different fungal lineages. In total 165 out of 202 genes involved in lipid metabolism were present in all tested fungal lineages, while remaining 37 genes were found to be absent in some of fungal lineages. Duplications were observed for 69 genes. For the first time we demonstrate that ergosterol is not being produced by several independent groups of plant-associated fungi due to the losses of different ERG genes. Instead, they possess an ancestral pathway leading to the synthesis of cholesterol, which is absent in other fungal lineages. The lack of diacylglycerol kinase in both Mortierellomycotina and Blastocladiomycota opens the question on sterol equilibrium regulation in these organisms. Early diverging fungi retained most of beta oxidation components common with animals including Nudt7, Nudt12 and Nudt19 pointing at peroxisome divergence in Dikarya. Finally, Glomeromycotina and Mortierellomycotina representatives have a similar set of desaturases and elongases related to the synthesis of complex, polyunsaturated fatty acids pointing at an ancient expansion of fatty acid metabolism currently being explored by biotechnological studies.